2017
DOI: 10.1002/admi.201700294
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Assisted Nanowelding of Graphene to Metals: An Optical Approach toward Ultralow Contact Resistance

Abstract: The electrical performance of graphene‐based devices is largely limited by substantial contact resistance at the heterodimensional graphene–metal junctions. A laser‐assisted nanowelding technique is developed to reduce graphene–metal (G–M) contact resistance and improve carrier injection in suspended graphene devices. Selective breakdown of CC bonds and formation of structural defects are realized through laser irradiation at the edges of graphene within the G–M contact regions in order to increase the chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…It should be noted that the interfacial interaction between the substrate and the prolonged edges of the GNR should be sufficiently strong to hold the edges in place as the GNR transforms into a nanoscroll. Strong interfacial interactions, attributed to the formation of chemical bonds, between graphene and common substrates such as metals (e.g., Au/Ni, Si, and SiOx) may be experimentally achieved by using various mechanisms like nanoscale welding , and different annealing protocols of rapid thermal annealing and vacuum annealing . Chemical bond formation has also been reported for other substrates such as Cu, Ni, and SiC. In addition, nonbonded vdW interaction between graphene and its target substrate may also be enhanced by techniques such as inserting a PMMA interlayer on top of SiO 2 and replacing SiO 2 substrate with atomically flat GaAs substrate, which may as well be explored in our proposed setup to fix the position of the prolonged edges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the interfacial interaction between the substrate and the prolonged edges of the GNR should be sufficiently strong to hold the edges in place as the GNR transforms into a nanoscroll. Strong interfacial interactions, attributed to the formation of chemical bonds, between graphene and common substrates such as metals (e.g., Au/Ni, Si, and SiOx) may be experimentally achieved by using various mechanisms like nanoscale welding , and different annealing protocols of rapid thermal annealing and vacuum annealing . Chemical bond formation has also been reported for other substrates such as Cu, Ni, and SiC. In addition, nonbonded vdW interaction between graphene and its target substrate may also be enhanced by techniques such as inserting a PMMA interlayer on top of SiO 2 and replacing SiO 2 substrate with atomically flat GaAs substrate, which may as well be explored in our proposed setup to fix the position of the prolonged edges.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the interfacial interaction between the substrate and the prolonged edges of the GNR should be sufficiently strong to hold the edges in place as the GNR transforms into a nanoscroll. Strong interfacial interactions, attributed to the formation of chemical bonds, between graphene and common substrates such as metals (e.g., Au/Ni, Si, and SiOx) may be experimentally achieved by using various mechanisms like nanoscale welding 51,52 and different annealing protocols of rapid thermal annealing and vacuum annealing. 53 Chemical bond formation has also been reported for other substrates such as Cu, Ni, and SiC.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Laser-assisted MOCVD (LMOCVD) is an ideal method for growth of various materials with the advantages of low growth temperature, fast growth rate, and the capability to deposit patterned materials. Several semiconductor materials, including silicon, gallium arsenide, indium phosphide, and aluminum nitride, have been successfully grown using LMOCVD. For instance, Zhou et al reported ultraviolet laser LMOCVD growth of c -oriented GaN films with a broad XRD peak at low temperatures. However, the photolysis of the precursors with a UV laser resulted in the low density of the reactive radicals and a slow GaN growth rate.…”
mentioning
confidence: 99%
“…As an example, the growth of inorganic nanostructures on CNT and rGO surfaces by direct laser irradiation of nanocarbon mixed with other precursors has been reported, leading to the formation of hybrid materials [112][113][114][115][116][117]. The laser-induced creation of structural defects and openended carbon atoms has allowed the nanowelding of graphene sheets to gold metal contacts at laser fluences below the ablation threshold of graphene [118]. After subsequent thermal annealing, graphene-metal junctions with ultra-low contact resistance were obtained in a precise manner, enabling a substantial performance enhancement in suspended graphene photodetectos.…”
Section: Treatments Based On Laser-activated Reactionsmentioning
confidence: 99%